How TVET is Reshaping Malaysia’s Economic Future - Wan Sharuzi, Wan Harun (UMPSA, 2025)
Once viewed as a secondary option to a university degree, Technical and Vocational Education and Training (TVET) is rapidly becoming the cornerstone of Malaysia’s economic strategy. Backed by substantial government investment, ambitious national policies, and soaring enrolment, TVET is being strategically positioned as a primary engine for building a high-skilled, future-ready workforce. As the nation charts its course towards 2030, this vocational revolution is not just about creating jobs; it’s about forging a new generation of innovators and industry leaders.